Peningkatan Hasil Belajar PAI Dengan Metode Pembelajaran Card Sord SDN 03 Binjai - Selvinora, Ayu (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve Islamic Religious Education (PAI) learning outcomes through the implementation of the Card Sort method in Grade IV students of SDN 03 Binjai, Tigo Nagari District, Pasaman Regency. This Classroom Action Research (CAR) was conducted in two cycles with 15 students as the subjects in the 2024/2025 Academic Year. The identified problems included the use of conventional methods without integrating technology or learning media, lack of variety in teaching models, low learning motivation, and minimal student initiative to ask questions, which negatively impacted learning outcomes. The success indicator was set at ≥70% of students achieving a Minimum Mastery Criterion (KKM) score of 70. In Cycle I, teacher activity reached 70%, student activity 80%, and learning mastery 63%. Cycle II demonstrated significant improvement, with teacher activity reaching 95%, student activity 95%, and learning mastery achieving 95%, thereby meeting the success criteria. The results indicate that the Card Sort method effectively improves PAI learning outcomes in Grade IV students of SDN 03 Binjai.